The Validity and Reliability of Social Responsibility Among Senior High School Students - Mar'atu Nafilah; Charmelia Nuraini; Nasya Dinda Afrillah (JEES: Journal of Education and Educational Sciences, 2026)
The purpose of this project is to create and verify a measurement instrument for evaluating high school students' social responsibility.  Data were gathered quantitatively from 248 kids who were chosen from a variety of metropolitan schools using purposive sampling.  Based on a theoretical framework of social responsibility, the instrument was validated both constructively using Exploratory Factor Analysis (EFA) and content by experts using the CVR and CVI methods.  Cronbach's Alpha and McDonald's Omega were used to assess for reliability, and both showed strong internal consistency (α > 0.80).  The findings point to a realistic and trustworthy factor structure with three primary dimensions: social justice, social culture, and contextual understanding. These results lend credence to the instrument's usage in educational settings, especially character education, for diagnostic and assessment purposes.  This study offers educators and policymakers a useful tool for assessing teenagers' social responsibility that is context-specific.  To assess the instrument's external validity in various institutional and cultural contexts, further study is advised.